Exploring the Execution Stack (Exploring the stack for fun and profit) - Rodriguez, Noemi; Moura, Ana Lúcia de (International Journal of Computer Architecture Education, 2015)
The Basic Software course offered at PUC-Rio adopts the perspective of a software developer, emphasizing the support that the basic components of a typical architecture provide for the abstractions offered by programming languages. A central topic of the course is the stack, a mechanism whose mastery is essential for programming proficiency. This work discusses how the course explores this mechanism and its support for typical programming abstractions, such as local variables and procedures, and also for application-level multitasking.